Studi Perbandingan Perusahaan Perseorangan (Sole Proprietorship) Dan Koperasi (Cooperative) Pada Negara Laos & Indonesia - Heriawan, Andi Rahmat (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
This study focused to conduct a comparative study of the legal form about individual company (Sole Proprietorship) and a Cooperative. This research using Normative legal research to examine legal rules related to corporate law in a country. The legal form of an individual company (sole proprietorship) is contained in the Laos "Enterprise Law" which was amended in 2013. Meanwhile, the cooperative in Laos is based on the "Enterprise Law", but the implementing regulations are subject to the "Decree On Cooperative" provisions, was made in 2009. The legal form of an individual company (sole proprietorship) in Indonesia is in Law No.3 of 1982, while cooperatives are contained in Law No.17 of 2017 concerning Cooperatives. The result of the research is that there are some fairly basic differences between individual companies (Sole Proprietorship) and Cooperative in Indonesia and Laos. This research have several comparative indicators can include the legal basis, company business activities, sources of capital, profits, losses, tax systems, and financing systems.